Assessing the impact of methotrexate, hydroxychloroquine, and their combination in rheumatoid arthritis: efficacy, safety, and cost analysis with vitamin D3 and BMI - Amanjot Kaur; Amandeep Singh; Amit Varma (Creative Pharma Assent, 2023)
Background: A chronic, symmetrical & inflammatory disease, which affects small joints and later progresses to involve large joints. To promote remission and control further joint destruction, disease modifying ant rheumatic drugs are used. The role of low Vitamin D3 and High BMI have been found in pathogenesis of RA. Methodology: The study was designed by Department of pharmacology and patients were enrolled from department of medicine. This was an open label; prospective study. After obtaining, informed written consent, the subjects were randomized in three groups, Group 1-Methotrexate 7.5-15mg once a week, Group 2 - Hydroxychloroquine 200mg BD and Group 3-Methotrexate 7.5mg once a week Plus HCQ 200mg OD. The Vitamin D3 levels and Body mass index was assessed at first visit. The quality of life was assessed using DAS-28/CRP, RAPID-3 Score. Average cost-effective ratio was also calculated. The adverse effects were also assessed using WHO-UMC causality assessment. The statistical analysis of the data Graph pad insta version 3.1 was used, p-value <0.05 was considered statistically significant. Results: The mean changes in DAS28/CRP and RAPID-3 between baseline & 16 weeks was highly significant (p<0.0001) in all groups. Vitamin D3 levels at baseline was 19.14±0.42, 19.86±0.67 and 19.52±0.98 in all groups respectively. Conclusion: The vitamin D3 levels were in the lower limit and BMI was raised in almost all the patients at first visit. The efficacy of combination therapy is found to be better when given at initial stages of RA patients